2018
DOI: 10.1021/acs.chemrev.8b00369
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Transition States and Drug Design

Abstract: Transition state theory teaches that chemically stable mimics of enzymatic transition states will bind tightly to their cognate enzymes. Kinetic isotope effects combined with computational quantum chemistry provides enzymatic transition state information with sufficient fidelity to design transition state analogues. Examples are selected from various stages of drug development to demonstrate the application of transition state theory, inhibitor design, physicochemical characterization of transition state analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 464 publications
(950 reference statements)
1
67
0
Order By: Relevance
“…Transition state analogues are generally efficient enzyme inhibitors, since in principle they are expected to bind more tightly to the enzyme than substrates themselves [ 186 ]. In the case of β-lactamases, a first transition state should involve the pre-formation of a tetrahedral carbon giving rise to a stable (in the case of SBLs) or high-energy (MBLs) tetrahedral intermediate.…”
Section: Mbl Inhibitors Based On Substrate Structuresmentioning
confidence: 99%
“…Transition state analogues are generally efficient enzyme inhibitors, since in principle they are expected to bind more tightly to the enzyme than substrates themselves [ 186 ]. In the case of β-lactamases, a first transition state should involve the pre-formation of a tetrahedral carbon giving rise to a stable (in the case of SBLs) or high-energy (MBLs) tetrahedral intermediate.…”
Section: Mbl Inhibitors Based On Substrate Structuresmentioning
confidence: 99%
“…The theory of tight binding between enzymes and transition state analogs is well-established and has guided the design of many inhibitors. 25,26 The lactonization step of this reaction is particularly amenable to the design of transition state mimics. It is a 5-exo-tet cyclization, with the carboxylate displacing the sulfonium group.…”
Section: Resultsmentioning
confidence: 99%
“…Crystal structures of FCP/SCP phosphatase were solved with AlF 4 − , in which the AlF 4 − complex acts as a phosphate analogue, inducing the proposed pentacoordinate phosphorane transition state of the hydrolysis reaction [51,53]. Enzymes recognize their substrates with high affinity, as an antibody to their haptens, which have been exhibited by X-ray crystallography [55,56]. In fact, we demonstrated that the phosphatase activities of FCP/SCP family phosphatases such as Fcp1 and Scp1 were strongly inhibited by AlF 4 − .…”
Section: Scp1 Substrate Identification By Pmpd Methods With Alf 4 −mentioning
confidence: 99%